2020
DOI: 10.1177/1077801220937782
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rape Myths and Current Events on the Well-Being of Sexual Violence Survivors

Abstract: Rape myths perpetuate blaming survivors of sexual violence for their own victimization. Although research has explored how public and political discourse, current events, and media coverage of sexual violence impacts the well-being of survivors, few studies have examined it from the perspectives of participants as a significant event is unfolding. This study presents findings from semi-structured interviews with female, trans, and nonbinary identified survivors during the Kavanaugh confirmation hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…Recognize social media can be both a supportive resource and/or a form of selfharm/unhealthy coping depending on how survivors are using their platforms mental health symptomatology. This is consistent with prior research which identified increases in distress among survivors during major news events involving sexual assault (e.g., Kavanaugh confirmation hearings; Anderson & Overby, 2021). Notably, though the current study was anchored in the #MeToo Movement as a reference point for survivors to think about their experiences, many participants recalled sexual assault stories on SM which preceded #MeToo (e.g., Brock Turner and Donald Trump), suggesting that the impacts of exposure are poignant enough to be recalled many years after the fact.…”
Section: Discussion and Clinical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…Recognize social media can be both a supportive resource and/or a form of selfharm/unhealthy coping depending on how survivors are using their platforms mental health symptomatology. This is consistent with prior research which identified increases in distress among survivors during major news events involving sexual assault (e.g., Kavanaugh confirmation hearings; Anderson & Overby, 2021). Notably, though the current study was anchored in the #MeToo Movement as a reference point for survivors to think about their experiences, many participants recalled sexual assault stories on SM which preceded #MeToo (e.g., Brock Turner and Donald Trump), suggesting that the impacts of exposure are poignant enough to be recalled many years after the fact.…”
Section: Discussion and Clinical Implicationssupporting
confidence: 92%
“…While #MeToo was intended to challenge rape culture, preliminary research on the digital movement suggest that victim blaming and hostile resistance to social change are still prevalent on SM platforms (Nutbeam & Mereish, 2021; PettyJohn et al, 2019). Exposure to narratives that uphold rape culture is concerning as it has the potential to exacerbate negative outcomes for survivors, including self-blame and increased trauma-related mental health symptoms (Anderson & Overby, 2021; Campbell et al, 2009; Kosloski et al, 2018; Schneider & Carpenter, 2019). Continuing research is needed to assess whether hashtag activism addressing sexual violence has altered the overall tone of public discourse on SM platforms, and how such tone is impacting users.…”
Section: #Metoo: Hashtag Activism On Social Mediamentioning
confidence: 99%
“…Researchers continue to find that people attribute blame towards victims of sexual violence based on factors such as alcohol or drug consumption, what the victim was doing or wearing, and their relationship with the perpetrator (Burgin & Flynn, 2021;Pinciotti & Orcutt, 2021). Such attitudes not only increase the harm experienced by victims, who may internalise these negative judgments, but also create barriers to help seeking (Anderson & Overby, 2021;Lichty & Gowen, 2021;Trottier et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…False beliefs about rape when victims are women have been well studied over the past 35 years (see Edwards et al, 2011, for a review). Researchers found relationships between female rape myth acceptance and less rape disclosure by victims (Egan & Wilson, 2012), more victim blaming attributions (e.g., Anderson & Overby, 2021; Kopper, 1996; St. George et al, 2021), and decreased willingness to intervene in potential sexual assault situations (McMahon, 2010).…”
Section: Male Rape Mythsmentioning
confidence: 99%